2015
DOI: 10.3892/or.2015.4445
|View full text |Cite
|
Sign up to set email alerts
|

Hispolon inhibits breast cancer cell migration by reversal of epithelial-to-mesenchymal transition via suppressing the ROS/ERK/Slug/E-cadherin pathway

Abstract: Hispolon has been shown to have anticancer effects on various tumors. However, whether hispolon exerts anti-migration activity in breast cancer cells and the underlying mechanisms, have not been elucidated yet. In the present study, our data demonstrated that hispolon inhibited TPA-induced breast cancer MCF-7 cell migration at sub-toxic concentrations in vitro. Hispolon decreased the level of cellular ROS significantly and repressed TPA-induced phosphorylation of extracellular signal-regulated kinase (ERK), ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 50 publications
(58 reference statements)
1
9
0
Order By: Relevance
“…We also observed that increased E-cadherin, Snail, Slug and Twist expression was associated with the malignant phenotype of PTs. Our findings were concordant with previous studies that showed that EMT markers (E-cadherin, Snail, Slug and Twist) expression ( P =0.025, P =0.001, P <0.01, P =0.044, respectively) correlated more strongly with borderline and malignant PTs than with benign PT [25]. However, no significant difference in N-cadherin ( P =0.146) expression was observed between the malignant/borderline and the benign groups.…”
Section: Discussionsupporting
confidence: 93%
“…We also observed that increased E-cadherin, Snail, Slug and Twist expression was associated with the malignant phenotype of PTs. Our findings were concordant with previous studies that showed that EMT markers (E-cadherin, Snail, Slug and Twist) expression ( P =0.025, P =0.001, P <0.01, P =0.044, respectively) correlated more strongly with borderline and malignant PTs than with benign PT [25]. However, no significant difference in N-cadherin ( P =0.146) expression was observed between the malignant/borderline and the benign groups.…”
Section: Discussionsupporting
confidence: 93%
“… Cancer type Cell line No. of cells/well Treatment time IC 50 Molecular targets Cell cycle arrest References Glioblastoma U87MG 1 × 10 4 24, 48, 72 h Cyclin D4↓, p2↑, p53↑, CDK4↓, p-ERK 1↓1 G2/M Arcella et al (2017) Cervical HeLa, SiHa 7 × 10 4 24 h p-AKT↓, ERK Act , LC3- II↑, MMP-2↓, MMP-9↓ Hsin et al (2017) Breast MCF-7, T47D, MDA-MB-231 5 × 10 3 , 5 × 10 4 24 h 70 Mm ERα↓, PARP↑, Bcl-2↓, E-cadherin↓, MMP-9↓, p-IκBα┴, p- NF-κB↓ ( Jang et al, 2015 ; Sun et al, 2015 ; Zhao et al, 2016 ; Wang et al, 2017 ) Naso-pharyngeal HONE-1, NPC-39, NPC-BM, NPC-039 5 × 10 4 p-Akt┴, uPA┴, MMP-2↓, MMP-9↓, caspase-3 Act , caspase-8 Act , caspase-9 Act ( Hsieh et al, 2014 ; Ho et al, 2017 ) Lung A549, H661 1 × 10 4 24, 48, 72 h 35.9 ± 6.9, 28.8 ± 3.1, 8.1 ± 2.3 μM Cyclin D1↓, CDK2↓, CDK4↓, cyclin E↓, CDK6↓, p27↑, p21↑ G0/G1 …”
Section: Biological Activities Of Hispolonmentioning
confidence: 99%
“…Metastasis is a primary cause of mortalities and most complicated obstacle in the development of effective cancer therapies ( Zhao et al, 2016 ). Metastasis is characterized by four important steps: detachment, migration and adhesion of cancer cells to secondary sites.…”
Section: Biological Activities Of Hispolonmentioning
confidence: 99%
“…Hispolon is an active phenol compound that is isolated from Phellinus linteus . It has various biological functions including anti–inflammatory, anti-oxidant, anti-proliferative, and anti-tumor effects [15]. Anti-tumor effect of hispolon has been shown through inhibition of cell growth, induction of cell cycle arrest and apoptosis, and inhibition of metastasis in various types of cancer [3,59].…”
Section: Introductionmentioning
confidence: 99%
“…Anti-tumor effect of hispolon has been shown through inhibition of cell growth, induction of cell cycle arrest and apoptosis, and inhibition of metastasis in various types of cancer [3,59]. Down-regulation of G1/S transition-related proteins [6,10], modulation of extracellular signal-regulated kinase phosphorylation [1], and reactive oxygen species-mediated mitochondria damage [9] were proposed to involvement in anti-cancer effect by hispolon. However, there have been no reports on the anti-tumor effects of hispolon in renal carcinoma cells.…”
Section: Introductionmentioning
confidence: 99%